Political Satire in Egypt after 2011: The effect of the second season of the satirical show “Al-Bernameg” (2012-2013) on the Egyptian audience - ElGabry, Radwa (AUC Knowledge Fountain, 2014)
The introduction of the political satire program "Al-Bernameg" (The Program) in Egypt has created massive discussion in the media related to the level of acceptance of Egyptians to this new format and its effects on the audience. Satirical programming has been a key part of political discourse in Western culture for some time and a part of global art for centuries. It has also been established that such programming is of particular influence on Western voters, who turn to this nature of programming before others in order to gather political information. This study sheds the light on the effects of this programming format on the Egyptian audience as well as the perception of the viewers of its content. The research relies on the uses and gratification theory as a starting point to analyze the heavy consumption of the program in a very short time and the cultivation theory to explore the effects of watching the program on the perception of the audience regarding the political content presented. A survey targeting the viewers of the show was conducted among a purposive sample of Egyptians (310 participants) to analyze the reasons for watching the program, frequency of watching and the effect of the content on their perception of the political news and political engagement and participation in Egypt. The findings of the survey explained the reasons for the audience usage of the program and their perception. In addition, the results of the survey indicated that the program has a major influence on the audience regarding their perception of the political situation; however, it does not affect their political engagement or participation. Viewers in Egypt perceive the program as an entertainment show, yet they also consider it as a source of news and become affected by its presentation of the political situation. The more the viewer watches the show, especially if he is not exposed to other sources of news, the more he becomes affected by its cynical presentation.